2017
DOI: 10.1016/j.foodchem.2017.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative capacity and binding affinity of the complex of green tea catechin and beta-lactoglobulin glycated by the Maillard reaction

Abstract: Major green tea catechin, epigallocatechin-3-gallate (EGCG), binds non-covalently to numerous dietary proteins, including beta-lactoglobulin of cow's milk. The effects of glycation of proteins via Maillard reaction on the binding capacity for polyphenols and the antiradical properties of the formed complexes have not been studied previously. Binding constant of BLG glycated by milk sugar lactose to EGCG was measured by the method of fluorophore quenching. Binding of EGCG was confirmed by CD and FTIR. The antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 40 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Then, K a of BBPI-G-EGCG was 5.91 × 10 4 M −1 and n was 1.02. This result showed that K a (both in the 10 4 range) and n of BBPI-G-EGCG were similar with those of BBPI-EGCG, which indicated that BBPI grafted with glucose did not affect the binding of protein and EGCG [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, K a of BBPI-G-EGCG was 5.91 × 10 4 M −1 and n was 1.02. This result showed that K a (both in the 10 4 range) and n of BBPI-G-EGCG were similar with those of BBPI-EGCG, which indicated that BBPI grafted with glucose did not affect the binding of protein and EGCG [17].…”
Section: Resultsmentioning
confidence: 99%
“…And then, the binding constant K a and the number of binding sites ( n ) can be calculated according to a double-logarithmic equation [17] as follows for the static quenching:log[F0FF]=logKa+nlog[Q]…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the research of proteins, carbohydrates and polyphenols have all became hot topics. Perusko et al 15 investigated the binding affinity of glycosylated b-lactoglobulin with EGCG through non-covalent interaction and the antioxidant properties of b-lactoglobulin-EGCG non-covalent complex. Results showed that the binding affinity between glycosylated b-lactoglobulin and EGCG was similar to that between b-lactoglobulin and EGCG.…”
Section: Introductionmentioning
confidence: 99%
“…When K q is higher than diffusion‐limited rate constant (1 × 10 10 L M −1 s −1 ), it could indicate a static quenching between a protein and a quencher (Perusko et al, ). And thus, the binding parameters can be calculated according to a double‐logarithmic Stern–Volmer equation: log[]()F0F/F=log0.25emKa+nlog[]Q0.12em …”
Section: Methodsmentioning
confidence: 99%